Rancang Bangun Simulator Kincir Pembangkit Listrik Floating Hydro - Dian Prabowo; Pujono Pujono (Accurate: Journal of Mechanical Engineering and Science, 2021)
Energy consumption in Indonesia is increasing every year, the fulfillment of the energy needed must be overcome. Energy is something that is really needed by anyone, from humans or animals to be able to do something or work. This energy is also abstract, its existence can be felt, but it is difficult to prove. Electricity needs of the community today are a basic need. Electricity usage is almost 24 hours nonstop. To cope with the increasing demand for electricity, it is necessary to utilize natural resources that can be used as new energy resources. The floating hydro power plant simulator is a hydroelectric power plant that utilizes the flow of water from a pump to drive a waterwheel, a device designed to make it easier for students to learn basic electrical engineering and fluid mechanics. The purpose of this design is to design and build a floating hydro power plant and test the tool. The design method used the VDI 2222 method approach, which includes planning, conceptualizing, designing, finishing. The results of the design were according to the method used, namely in the form of a waterwheel simulator design for power plants. The estimated production process time for the manufacture of a floating hydro simulator for cutting 3.9 hours; process of gurdi 3.08 hours; lathe process 1.3 hours; 1.58 hours assembly process; finishing process 2.75 hours = 1.2 days (1 day = 8 hours). The total cost of making the machine was Rp. 2.605,740.00. The driven pulley test results in 65.4 rpm and the driven pulley produced 304 rpm and the output was 12.3 volts.